Pelaksanaan Sistem Informasi Akuntansi Pembayaran Klaim Jaminan Hari Tua Pada BPJS Ketenagakerjaan Mojokerto - Latifah Rukmiati Ifnu Jafar; Siti Ning Farida (Anggaran : Jurnal Publikasi Ekonomi dan Akuntansi, 2024)
In this research, the problem faced is that many customers want to file a claim at BPJS Ketenagakerjaan Mojokerto, but often fail or are delayed. The number of workers filing claims has increased, including those who have been laid off or whose contracts have ended. In addition, many participants postpone filing their claims until Hari Raya gets closer, which causes the queue for Old Age Security claims to increase.This journal was written using a qualitative descriptive approach. The focus of the research is the problems related to the implementation of the accounting information system for the payment of old-age security claims at BPJS Ketenagakerjaan Mojokerto. Theoretical studies are used to analyze the data obtained, selected, and processed. The results show that the process of paying Old Age Security claims at BPJS Ketenagakerjaan Mojokerto is in accordance with the accounting information system